Analisis Debit Banjir Rencana Daerah Tangkapan Air Waduk Tugu Menggunakan HEC-HMS - Anas Zulfikar Rasyid; Suharyanto Suharyanto; Robert Johanes Kodoatie; Yogi Pandhu Satriyawan (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
Over the course construction of Tugu Reservoir, it is proposed to build a spillway gate to increase its performance as a flood control infrastructure. The construction planning of spillway gate requires a calculation of design flood discharge for Tugu Reservoir Catchment Area. The latest calculation was carried out during its construction planning in 2010. Therefore, it is necessary to evaluate and recalculate the design flood discharge using the latest data. This study aims to model design flood discharge of Tugu Reservoir Catchment Area using HEC-HMS software. This software is able to simulate rainfall-runoff modeling in a catchment area. Based on field conditions, Tugu Reservoir catchment has parameters, curve number value of 79, impervious value of 5%, and a lag time of 4.81 minutes. The result of the HEC-HMS modeling shows that the design flood discharge of Tugu Reservoir for Q100 is 369,30 m3/s; Q1000 is 656,70 m3/s; and QPMF is 995.30 m3/s. Based on the test using Creager Graph, the design flood discharge for Tugu Reservoir is still in the reasonable category with C value below 100. The result of the HEC-HMS modeling is not much different from the calculation result of Tugu Reservoir Construction Planning in 2010.